Comparison Between Fetal Abdominal Subcutaneous Tissue Thickness and Abdominal Circumference to Predict Large for Gestational Age Neonate in Gestational Diabetes - Smitha Mohan; Pallavee P; Rupal Samal (Tehran University of Medical Sciences, 2024)
Objective: Increased subcutaneous fat deposition in abdomen in large for gestational age (LGA) fetuses of mothers with gestational diabetes mellitus can be measured by fetal abdominal subcutaneous tissue thickness (FASTT) using ultrasound. The current study aimed to evaluate the correlation between FASTT and birth weight and compare FASTT and abdominal circumference (AC) for prediction of LGA babies in gestational diabetes. Materials and methods: 150 term GDM women were enrolled into the study. FASTT was measured weekly. Birth weight was measured immediately after delivery and categorized into SGA, AGA and LGA according to International growth charts. The last FASTT and AC values were recorded for analysis. Correlation statistics was used to determine the relation between FASTT with birth weight and ROC curves were used to compare FASTT and AC for prediction of LGA fetuses. Results: There was weak positive correlation between FASTT and birth weight with Pearson's co-efficient (r) of 0.375. The cut-off value for FASTT to predict LGA fetuses obtained by ROC curve was ≥8.05 mm with sensitivity and specificity of 68.8% and 68.7%. The mean values of FASTT for small for gestational age (SGA), appropriate for gestational age (AGA) and LGA fetuses were significantly different. AUC for FASTT was 0.692 and for AC was 0.755. Conclusion: FASTT had a positive but weak correlation with birth weight. The utility of FASTT as a screening tool may not be impressive. FASTT can discriminate between SGA, AGA and LGA fetuses. AC is a better predictor than FASTT for LGA neonates.